Model Pembelajaran Akidah Akhlak Melalui Religious Culture Di Min Blora Dan Mi Taris Pati - Elya Umi Hanik (Universitas Islam Lamongan, 2017)
Abstrack: The one of problem for student is dcreasing moral, in this case, study akidah akhlak seeks to establish personal morals learners in terms akidah and akhlak. Learning akidah akhlak not only focused on cognitive aspects but also the establishment of affective and psychomotor through religious culture that will ultimately achieve the goal of learning is the formation of the character of the students. This study aims to 1) analyze the application of akidah akhlak learning through religious culture in Islamic Elementary School (MIN) Plosorejo, Blora and Islamic Elementary School Tarbiyatul Islamiyah Winong, Pati. 2) analyze the effects of Akidah Akhlak learning to form the students’ characters through religious culture in Islamic Elementary School (MIN) Plosorejo, Blora and Islamic Elementary School Tarbiyatul Islamiyah Winong, Pati. This research is multi-case qualitative in Islamic Elementary School (MIN) Plosorejo, Blora. And 2) Islamic Elementary School Tarbiyatul Islamiyah Winong, Pati. Data collection was done through deep interviews, documentations, and observations. Some steps used to have data validity involved zealous observation, triangulations, and enough references. The analysis was done by following the data collection steps, data reduction, data presentation, and verification. The results of the study included 1)The learning process of Akidah Akhlak was done contextually in the form of well learning whether inside or outside of the class through various learning methods involved modeling, discipline, habit, punishment and reward, and motivation. In the implementation of religious values, these hierarchies of steps were done as follows: creating religious value, speeches and advises, models, habit, extracurricular activity, posters with Hadist or motivating words which were attached to the wall, forming the leader’s soul through religious activity. 2) The effects of Akidah Akhlak learning through religious culture in Islamic Elementary School Plosorejo, Blora and Islamic Elementary School Tarbiyatul Islamiyah Winong, Pati were able to form the students’ characters in the expectation of religious values, independent, communicative, discipline, caring about surrounding, responsible, social care, and willing to know, and secondly to form the students’ achievement in every side of academic.Kaywords: Moral Learning, Students Character, Religious Culture